Helicity and topological charge tunable optical vortex based on a Hermite-Gaussian beam dynamically controlled folded-cavity resonator - Lin, Shibing; Wang, Deen; Zheng, Yamin; Guo, Liquan; Zhang, Yifan; Zhuang, Yongchen; Huang, Lei (Frontiers in Physics, 2023)
Helicity and topological charge are two important characteristic parameters to the application of vortex beam, including optical communications, optical manipulation and material processing, etc. In this work, a helicity and topological charge tunable vortex laser based on a folded resonant cavity is presented. In the resonant cavity, a Z-shaped structure is adopted and two deformable mirrors (DMs) are cascaded into the cavity as intro-cavity modulation elements. By applying different voltage combinations to the DMs, the Hermite-Gaussian (HG) beam with different indices and distribution orientations θ could be generated from the Z-shaped folded-cavity resonator. The vortex beam with tunable helicity and topological charge is realized by using an extra-cavity astigmatic mode converter to transform the generated HG beam, and the simulation results verified the feasibility of the presented vortex laser. In the experiment, the HG_(m,0)^θ beam (m=1 to 10 and θ =-90° to 90°]) and the vortex beam (topological charge l from ±1 to ±10 and left/right helicity) were flexibly achieved through numerically adjusting the driving voltage combinations of the intra-cavity cascaded DMs.